PENGEMBANGAN BAHAN AJAR EKONOMI BERBASIS PROBLEM BASED LEARNING DALAM BENTUK BUKU SAKU DIGITAL - Zakiyyah Ul Haque; Riza Yonisa Kurniawan (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Abstract:Teaching materials are educational resources for transferring knowledge, but the ineffectiveness of teaching materials can be an inhibitors in achieving the learning objectives. The research on development digital pocket books based on Problem Based Learning (PBL) aimed to explain the level of feasibility; analyzed effectiveness through learning outcomes; as well as knowing the practicality of using digital pocket books in the learning process. Type of the research was a R&D (Research and Development) used the ADDIE model by Dick & Carry. The research procedure consisted of five stages, analysis, design, development, implementation, and evaluation. The research subjects were 20 students of class XI Science. Data collection techniques through interviews, questionnaires, and tests. Data analysis techniques are (1) expert analysis and validation; (2) student questionnaire responses; and (3) gain score calculation. The results showed that the digital pocket book "very feasible" was used by getting a percentage score of eligibility of 83.77% and practicality of 88%, as well as getting a gain score of 0.64 with the criteria of "moderate". Based on these results, PBL-based digital pocket books are declared very feasible and practical to use during the learning process because it can increase the learning outcomes.Keywords: Teaching Materials, Digital Pocket Book, Economic, Problem Based Learning